Faktor-Faktor Yang Mempengaruhi Struktur Modal Pada Perusahaan Publik Di Sektor Manufaktur (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
The purpose of this study was to determine the effect of Profitability, Asset Structure, and Dividend Policy on Firm’s Capital Structure in Manufacturing Companies that listed in Indonesia’s Stock Exchange in the period of 2017-2019. The sampling method used was Purposive Sampling with 103 data of total sample. Data processed using multiple regression analysis which is done through SPSS software. The result showed that Profitability have negative and significant influence on Capital Structure, Asset Structure and Dividend Policy have no significant influence on Capital Structure. The implication of this study is the need to increase firm’s profitability that will reduce firm’s debt.